Teaching Nigerian Arabic Poetry Based On Ethics: The Poem â€œFighting Fraudâ€ By Osman Idris Al-Kanqawi As A Model/ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø´Ù‘Ø¹Ø± Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„Ù†Ù‘ÙŠØ¬ÙŠØ±ÙŠ Ø¹Ù„Ù‰ Ø£Ø³Ø§Ø³ Ø§Ù„Ø£Ø®Ù„Ø§Ù‚: Ù‚ØµÙŠØ¯Ø© "Ù…ØØ§Ø±Ø¨Ø© Ø§Ù„ØºØ´Ù‘" Ù„Ø¹Ø«Ù…Ø§Ù† Ø¥Ø¯Ø±ÙŠØ³ Ø§Ù„ÙƒÙ†ÙƒØ§ÙˆÙŠ Ø£Ù†Ù…ÙˆØ°Ø¬Ø§ - Abdus-Salam, Ambali Babatunde; Yakub, Muhammed Jamiu (Ijaz Arabi Journal of Arabic Learning, 2020)
The literary productivity of Nigerian Arabic poets greeted with modern trends experienced multidimensional influences. Thus, social issues became literary themes, especially ones that relate to significant national challenges in the educational sector. This paper:Â Teaching Nigerian Arabic Poetry Based On Ethics: The Poem â€œFighting Fraudâ€ By Osman Idris Al-Kanqawi As A Model,Â therefore, focused on the poetic work of a Nigerian Arabic poet on instructional issues. The objectives of the study include: (i) establish the availability of Arabic poetry on educational challenges in Nigeria, (ii) analyze the content in the light of Moral and psychological guides, (iii) examine the instructional objectives of the chosen poet. The study adopted both historical and descriptive methods.